Conflicts Between Women's Religiosity and Sense of Free Will in the Context of Elective Abortion: A Qualitative Study in the Worst Period of Italy's COVID-19 Crisis - Testoni, Ines; Finco, Nicoletta; Keisari, Shoshi; Orkibi, Hod; Azoulay, Bracha (Frontiers in Psychiatry, 2021)
This qualitative study considers the relationship between abortion, bereavement, and the effects of the COVID-19 lockdown nine women who had undergone an elective abortion, which is voluntarily termination of a pregnancy at the woman's request. These women were interviewed in three time points (1 month, 6 months, and 1 year after the event) to consider the possible evolution of their experience. The third phase was concurrent with the COVID-19 pandemic and particularly with Pope Francis's Easter declaration against abortion. All the interviews were conducted and analysed through qualitative research in psychology. Results showed that the abortion experience led to physical, relational, and psychological suffering, similar to perinatal grief. Participants were non-practising Catholics and religiosity did not help them to overcome their sorrow. Though religiosity is a possible resilience factor in other stressful conditions, in this case it is a factor that aggravated suffering. Finally, we discuss the difficulties experienced by Catholic women who choose to have an abortion and assert the necessity of psychological and spiritual interventions to support these women.